2019
DOI: 10.3390/healthcare7020064
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Governments in the Implementation of Patient Safety and Patient Safety Incident Reporting in Indonesia: A Qualitative Study

Abstract: (1) Background: A patient safety incident reporting system was introduced in Indonesian hospitals in 2006; however, under-reporting of patient safety incidents is evident. The government plays a vital role in the implementation of a national system. Therefore, this study focuses on how the Indonesian government has been undertaking its role in patient safety at provincial and city/district levels, including incident reporting according to the National Guideline for Hospital Patient Safety. (2) Methods: This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…A lack of feedback has been previously acknowledged as a weakness in incident reporting. 24,25,28 Conversely, properly conducted feedback results in specific improvements that are necessary to enhance incident reporting. 29 Most of the supervisorial and managerial level staff interviewed highlighted a lack of knowledge and lack of socialization as barriers; they must urgently be made aware of this discrepancy between their perspectives of barriers and the need for feedback reported by staff.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of feedback has been previously acknowledged as a weakness in incident reporting. 24,25,28 Conversely, properly conducted feedback results in specific improvements that are necessary to enhance incident reporting. 29 Most of the supervisorial and managerial level staff interviewed highlighted a lack of knowledge and lack of socialization as barriers; they must urgently be made aware of this discrepancy between their perspectives of barriers and the need for feedback reported by staff.…”
Section: Discussionmentioning
confidence: 99%
“…To provide well-qualified healthcare services, medical establishments should meet basic requirements, should apply the process of patient safety perfectly in a flawless way, and should perform processes with the appropriate procedure. Health institutions are generally held responsible for the establishment of safety reporting systems by governments [24], in which medication safety, transfusion safety, surgical safety, patient falls, and so on are included. Corrective and preventive actions should be taken for reported events [25].…”
Section: Definition Of Medical Errormentioning
confidence: 99%
“…According to [81], the similarity between two IVIF sets A and B is S A, B = E M A, B , where "E" represents an IVIF entropy measure. Based on the given entropy calculations (Wu et al, 2014), it is possible to rearrange the similarity formula as follows: (24). These values are used to calculate 1.3 = 0.92).…”
Section: Preliminariesmentioning
confidence: 99%
“…District health offices (DHOs) oversaw both the public and private sectors 11. A study identified numerous macrolevel, mesolevel and microlevel issues regarding patient safety and patient safety incident reporting, including inadequate government monitoring and assessment, DHOs and the provincial health office not being involved in incident reporting, a lack of government funding for hospitals, a lack of commitment and priority for patient safety, and a lack of systematic partnership and collaboration between patient safety agencies and DHOs or the provincial health office 12. Despite identical ownership and accreditation status, the authors discovered disparities in implementation of patient safety projects and activities.…”
Section: Introductionmentioning
confidence: 99%